Surrogacy in Islamic Jurisprudence: A Comprehensive Study of Maqasid al-Shariah and Ethical Viability According to Contemporary Mufassir - Angga Tinova Yudha; Amsal Qori Dalimunthe; An Nisa Dian Rahma (Pharos Journal of Theology, 2025)
From an Islamic Jurisprudence point of view, this research tries to examine surrogacy mostly in connection to Maqasid al-Shariah and current mufassir ideas. For many couples fighting infertility in the era of globalization and sophisticated reproductive technology, surrogacy has grown to be a treatment. Studying the ethical viability and legal status of surrogacy, this research bridges the need of knowing the Islamic legal view on major technical developments. Employing descriptive approaches and qualitative methods, this study gathers and analyses data from two major sources: academic sources and modern readings—that is, Quran and Hadith texts. It seeks to unite academic viewpoints, then. Using the Miles, Huberman, and Saldana approach, this work presents a conceptual visual representation of surrogacy in Islamic circumstances. The results reveal among academics a mosaic of several viewpoints. Some reject conventional surrogacy, citing concerns over the sanctity of family relationships and questions of parenthood, but others accept certain modifications of gestational surrogacy as allowable. By investigating how rules governing surrogacy might either promote or obstruct the goals of Maqasid al-Shariah, this study emphasizes the need of protecting wealth, life, knowledge, next generations, and values. Maintaining both physical and mental health, gestational surrogacy is attracting more interest as it also respects religious and cultural norms. Particularly when it comes to crafting a legislative framework honoring Islamic values while meeting present practical needs, this study underlines the need of constant debate and broad consensus among intellectuals, medical professionals, and the Muslim community.